Produção heteróloga, em sistema procarioto, de proteínas estruturais dos vírus Zika e Chikungunya e avaliação de seu potencial para o uso em ferramentas diagnósticas - Flavia Fonseca Bagno (2018)
Arboviruses have become a public health problem causing large epidemics worldwide. The clinical similarities, cross-reactivity and cocirculation of the arboviruses in Brazil such as Dengue virus (DENV), Chikungunya virus (CHIKV), Zika virus (ZIKV), and Yellow fever virus (YFV) have complicated the diagnosis of these infections, highlighting the need of new diagnostic tools. In previous studies, envelope proteins of these viruses have been shown to be immunodominant and associated with the generation of antibodies, and are, therefore, strategically important in serological diagnosis. This study aimed to express ZIKV and CHIKV proteins with antigenic potential in prokaryotic system. The nucleotide coding sequences of the ZIKV-E, CHIKV-E1 e CHIKV-E2 were analyzed in silico, commercially synthesized, cloned in pET-21 and expressed in Escherichia coli BL21 (DE3). Recombinant proteins were purified by affinity chromatography and evaluated for their antigenic potential in mice and human sera. Western blot assays confirmed the reactivity of the recombinant proteins, which were recognized by the anti-his and antibodies in the infected mice sera. Among the proteins produced, CHIKV-E1 showed a great potential for serological diagnosis considering the ELISA results, while the others require additional improvement. Since proteins have been successfully generated and the initial CHIKV18 E1 analyzes are promising, further studies should be carried out, looking for a better use of these proteins in specific diagnosis of CHIKV and ZIKV infections.